Optimization Of State Investment Governance Based On Meaningful Participation In Order To Realize The General Principles Of Good Government (AAUPB) And The Rule Of Law Indonesia - Daulat Nathanael Banjarnahor; Firinta Togatorop; Abather Rahi Saadoon (Cattleya Darmaya Fortuna, 2026)
Throughout the history of the Indonesian government, various dynamics and changes have occurred, resulting in various regulations and laws in response to the diverse problems and challenges facing the country. These issues include: inconsistencies or overlaps between regulations and laws, conflicts between the central and regional governments, and conflicts over the division of authority between state ministries and state institutions. However, throughout the history of the Indonesian government, numerous studies on the obstacles to investment in Indonesia have identified several major obstacles. Another issue related to investment in Indonesia is the management of the State Budget (APBN) for investment activities undertaken by the Indonesian government. Several examples of problematic Indonesian government investments have been cited, most of which are suspected of experiencing problems in the form of alleged corruption involving large amounts , errors in governance, poor transparency or openness, inadequate planning, and other issues. Therefore, optimizing state investment governance is crucial. based on meaningful participation can be offered as a solution in order to create an investment climate that is in accordance with the general principles of good governance (AAUPB) and the realization of Indonesia as a state of law